2011
DOI: 10.1002/pen.22003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acrylonitrile content and molecular weight on the scratch behavior of styrene‐acrylonitrile random copolymers

Abstract: Fundamental understanding of the scratch behavior of styrene-acrylonitrile (SAN) random copolymers with variation in acrylonitrile (AN) content and molecular weight (MW) is pursued using the methodology outlined in ASTM D7027-05/ISO 19252:08. Two sets of SAN model systems are employed: One that varies the AN content with similar MW and another that varies the MW at the same AN content. Key scratch damage mechanisms (scratch groove formation, periodic micro-cracking, and plowing) are identified and correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…In general, a lower SFC leads to higher scratch resistance [18]. The SFC can often give valuable clues to the location of transitions in scratch deformation mechanisms [14].…”
Section: Scratch Testmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, a lower SFC leads to higher scratch resistance [18]. The SFC can often give valuable clues to the location of transitions in scratch deformation mechanisms [14].…”
Section: Scratch Testmentioning
confidence: 99%
“…The scratch friction coefficient (SFC) was calculated by dividing the tangential force (F t ), continuously measured, by the applied normal force (F n ) [14] and allowed one to compare the scratch resistance of the tested materials. In general, a lower SFC leads to higher scratch resistance [18].…”
Section: Scratch Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Bellemare et al [18] reported a decrease in pile-up height (shoulder height) with the increase in strain hardening exponent using pure Copper and Copper/Brass alloy. Browning et al [2] showed that, using experimental study on styrene-acrylonitrile (SAN) random copolymers, an increase in acrylonitrile (AN) content or molecular weight (MW) can have a positive effect on improving the scratch resistance as it increases the tensile strength and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…For those soft films it was shown that inclusion of AN was an effective method for tuning the modulus of the films 8 . AN is known to increase the surface hardness 25 , modulus 26 and tensile strength 27 and thermal stability 28,29 of copolymers due to the strong polarity of nitrile groups 28 and strong molecular interactions 30 . However, all of our previous nanostructured ionomer films used Bd as the main structural monomer 9,23,24 .…”
Section: Introductionmentioning
confidence: 99%